Evidence for sustained physiological adaptation between consecutive exercise bouts at simulated altitude - Kelsey E. Joyce; M. Travis Byrd; Courtney M. Wheatley‐Guy; Jesse C. Schwartz; Jordan K. Parks; Bruce D. Johnson (Physiological Reports)
Abstract Intermittent hypoxia has been used to enhance oxygen delivery in athletes and patients; however, it is unclear whether acute exposure is sufficient to elicit lasting physiologic adaptation(s). The purpose of this study was to evaluate physiologic response(s) to hypobaric‐hypoxic (HH) exercise. Nine participants (4 M/5F; 37.9 ± 12.7 yrs.; 174.3 ± 9.4 cm; 75.3 ± 15.9 kg; 24.4 ± 3.4 kg/m2) were exposed to progressively higher simulated altitudes and completed two HH submaximal exercise sessions (~30 min ea., ≥72 h apart) on a cycle ergometer at the first altitude that posed a significant challenge to them. Altitude was dependent on individual response as determined from heart rate (HR), peripheral oxygenation (SpO2), and the ratio of HR response to SpO2 (HR/SpO2). Statistical analyses included paired samples t‐test (p ≤ 0.05). No significant change in SpO2 (HH‐1: 85 ± 4% vs. HH‐2: 85 ± 4%, p = 0.684) was observed between sessions. However, there were significant decreases in: HR (HH‐1: 150 ± 18 bpm vs. HH‐2: 133 ± 27 bpm, p = 0.001) of 18 bpm (11%); HR/SpO2 (HH‐1: 1.76 ± 0.22 vs. HH‐2: 1.57 ± 0.33, p = 0.012); and RPE (HH‐1: 15 ± 2 vs. HH‐2: 11 ± 4, p = 0.017). While workload significantly increased (HH‐1: 89 ± 36 W vs. HH‐2: 105 ± 36 W, p = 0.024). Some participants had a threshold/challenging altitude, but from a single bout there is evidence of improved tolerance that can last over a week. Further investigation is required to replicate and understand possible mechanisms.